Activation of the language control network in bilingual visual word recognition. (February 2019) - Peeters, David; Vanlangendonck, Flora; Rueschemeyer, Shirley-Ann; Dijkstra, Ton
Abstract: Research into bilingual language production has identified a language control network that subserves control operations when bilinguals produce speech. Here we explore which brain areas are recruited for control purposes in bilingual language comprehension. In two experimental fMRI sessions, Dutch-English unbalanced bilinguals read words that differed in cross-linguistic form and meaning overlap across their two languages. The need for control operations was further manipulated by varying stimulus list composition across the two experimental sessions. We observed activation of the language control network in bilingual language comprehension as a function of both cross-linguistic form and meaning overlap and stimulus list composition. These findings suggest that the language control network is shared across bilingual language production and comprehension. We argue that activation of the language control network in language comprehension allows bilinguals to quickly and efficiently grasp the context-relevant meaning of words.